Autophagy involvement in T lymphocyte signalling induced by nickel with quantitative phosphoproteomic analysis - Gong Wang; Tingting Shen; Xueyan Huang; Zhen Luo; Yulong Tan; Genlin He; Zeze Wang; Ping Li; Xiaoqian Liu; Xueting Yu; Boyi Zhang; Huan Zhou; et al. (Ecotoxicology and Environmental Safety, 2022)
Nickel-induced allergic contact dermatitis (ACD) is a common skin disease. The mechanism by which nickel causes ACD is not clear. There is no treatment for it, only symptomatic therapy. However, due to the lifetime sensitization characteristics, the recurrence rate in patients is high. T lymphocytes play a key role in nickel-induced ACD. Elucidating the potential mechanism underlying nickel-induced T lymphocyte signalling might make it possible to achieve targeted treatment of nickel-induced ACD. In our study, a phosphoproteomic approach based on tandem mass tag (TMT) labelling and LCMS/MS analyses was employed. An animal model of nickel allergy was established. Splenic T lymphocytes were purified for quantitative phosphoproteomic analysis. The numbers of phosphoproteins, phosphopeptides and phosphosites identified in this study were 3072, 7977 and 10,200, respectively. Comprehensive gene ontology (GO) analysis combined with Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed that nickel can significantly affect the phosphorylation of the mTOR signalling pathway in T lymphocytes. Western blotting analysis was used to detect changes in the expression of autophagy-related proteins (Beclin 1, LC3II, and p62). Nickel allergy changed autophagy-related protein expression (p < 0.05). It has been demonstrated that nickel causes autophagy of T lymphocytes in the spleen. Using autophagy inhibitors to intervene, it was found that Th1 differentiation was inhibited, and the expression of Th1-related inflammatory factors was downregulated. Overall, the identification of relevant signalling pathways yielded new insights into the molecular mechanisms underlying nickel allergy and might help in the discovery and development of mechanism-based drugs.